Half car active suspension system - Basari, Amat Amir; Salam, Saifullah; Abdul Aziz, Khairul Azha; Abdul Manap, Redzuan (2012)
This paper presents a new method in modeling an active suspension system for a half-car model in state space form and develop a robust control strategy in controlling the active suspension system. Fuzzy logic is used to control the system. Velocity and displacement of front wheels are taken as input variables of the fuzzy logic controller. Active forces improving vehicle driving, ride comfort and handling properties are considered to be the controller outputs. The controller design is proposed to minimize chassis and wheels deflection when uneven road surfaces, pavement points, etc. are acting on the tires of running cars. Comparison of performance of active suspension fuzzy control system with passive suspension system is shown using Matlab/Simulink simulation. From the result, it shows that active suspension system has better performance than the passive suspension system.